Enhancing Hajj Pilgrim Satisfaction: A Strategic Analysis of Service Quality Dimensions using the Analytic Hierarchy Process (AHP) in Alignment with Saudi Vision 2030 (Global Journal of Management and Business Research, 2024)
Saudi Arabia every year receives more than two million Muslims from all over the world to perform the Hajj the Muslim pilgrimage to Makkah To manage and satisfy such crowd Considering the variety of cultures languages and different levels of socio-economic background is next to impossible Saudi vision 2030 has taken it as its duty to ensure that pilgrimages will have joyful experience and good memories to take back home Authorities develop four categories of packages based on quality dimensions to meet different budgets To manage and provide quality service for the pilgrimages is incredibly challenging task In an effort from the authors to direct their research towards this goal A multi criteria decision model MCDM is developed to evaluate the service quality dimensions SQD and identify essential criteria that achieve pilgrim s satisfaction and keep up with hajj vision 2030 The aim is to provide an easy tool though a scientific one for companies providing these packages to adjust their services to match pilgrims expectations The Analytic Hierarchy Process AHP a well-known methodology is chosen to develop a selection model to help both companies and pilgrims make the best of the Hajj experience
Keywords: Analytic Hierarchy Process; AHP; Service Quality; SQD; MCDM; Hajj; Saudi Arabia